El cabildo catedral de Valladolid de Michoacán durante la gestión episcopal del Obispo Martín de Elizacoechea, 1745-1756 - Tavera González, Isabel (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
In the present investigation we analyze the management of that group of capitulars who governed the ecclesiastical Council of Valladolid de Michoacán during the bishopric of Martín de Elizacoechea in the years 1745 to 1756. We pay attention to two factors: on the one hand, we consider it necessary to know the structure and function of the perks as well as the persons in charge of the Council, paying attention on their ecclesiastical and academic formation. And on the other hand, we take care analyzing their position on the issues that concentrated more interest in the corporation, in order to keep its benefits safe, since in these years the Council enjoyed a considerable increase in its main income, that is, the tithe. However, it was also the period when the relationship between the Crown and the Church changed. The fiscal measures that the new Bourbon regime applied to American churches since the beginning of the Eighteenth Century generated an understandable concern for the privileged with respect to their rich resources, especially from two issues: the royal decree that ordered the payment of the debt of major and minor vacancies and the lease of the ninth royals that until then had been granted to the council.

En la presente investigación analizamos la gestión de aquel grupo de capitulares que gobernó el Cabildo eclesiástico de Valladolid de Michoacán durante el obispado de Martín de Elizacoechea en los años de 1745 a 1756. Ponemos atención en dos factores: por un lado, consideramos necesario conocer la estructura y función de las prebendas, así como a los personajes que estuvieron al frente del Cabildo, poniendo cuidado en su formación eclesiástica y académica. Y, por otro lado, nos ocupamos de analizar su postura ante los asuntos que concentraron mayor interés en la corporación en función de mantener a salvo sus beneficios pues en estos años el Cabildo gozaba de un aumento considerable de su principal ingreso, es decir, el diezmo. Sin embargo, también fue el periodo en que la relación entre Corona e Iglesia cambió, las medidas fiscales que el nuevo régimen borbón aplicó a las iglesias americanas desde inicios del siglo XVIII generaron una preocupación comprensible para los prebendados respecto de sus caudales. Sobre todo, a partir de dos asuntos: la real cédula que ordenó el pago de la deuda de vacantes mayores y menores y el arrendamiento de los reales novenos que hasta entonces había sido concedido al Cabildo.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2020-0729; Iglesia; Corona; Capitulares; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2854